PERBEDAAN ANTARA POLA TIDUR SISWA SMP SEBELUM DAN SAAT KEGIATAN BELAJAR DARI RUMAH DIBERLAKUKAN SELAMA PANDEMI COVID-19 - Jesica Angel Demak Taruli Butarbutar (2021)
The COVID-19 pandemic has changed how students learn by implementing a school from home system which carried out online. This system forces students to do plenty of assignments, thus disrupting sleep patterns. Though sleep patterns are very important for children and adolescents to maintain their health. The objective of this study is to discover the difference between the sleep patterns of junior high school students before and during school from home system was implemented due to COVID-19 pandemic. This research was an observational analysis with cross-sectional design at SMP Marsudirini Bekasi in December 2020 which involved 173 students. Sleep patterns were measured using a modified "Sleep Questionnaire" made by Stanford Health Care. Data analysis using Wilcoxon test. Results showed that the night sleep duration before school from home was 1 hour longer than during school from home (p value < 0.001). The duration of naps during school from home was 1 hour longer than before school from home (p value < 0.001). Total sleep duration per 24 hours during school from home was 1 hour longer than before school from home (p value = 0.005). In conclusion, during school from home students of SMP Marsudini Bekasi have a shorter nighttime sleep duration, longer daytime nap duration, and longer total sleep duration per 24 hours, compared to before school from home.